Marker identification for mastitis and its association in Thai-Friesian cattle in Northern Thailand - Chomdej,S. (Medwell Publishing, 2015)
The objective of this research is to find molecular markers for mastitis which are associated with diseased and non-diseased cows in Northern Thailand (Chiang Mai and Lamphun) by using Amplified Fragment Length Polymorphism (AFLP) and studying the association between discovered markers and mastitis. Three DNA sequences (A3, A7 and A8) among 12 sequences generated by AFLP which differ between cows with and without mastitis showed a similarity with previously described genes: PDZ domain containing 1 (PDZK1) and sodium channel protein type 8 subunit alpha (SCN8A). Four Single-Nucleotide Polymorphisms (SNP) were detected: G>T, T deletion and C>T (SCN8A-10 and SCN8A-54). Association analysis between genotypes of each gene and phenotype (diseased or non-diseased and somatic cell count) showed that SNP SCN8A-54 is associated with mastitis (p<0.01) and subclinical mastitis (p<0.01). This study demonstrated new molecular markers associated with bovine mastitis of the Thai-Friesian cattle breed in northern Thailand. © Medwell Journals, 2011.